Studi Perancangan Dan Pemanfaatan TPS 3R Untuk Sampah TPS (Tempat Pengolahan Sampah Rumah Tangga - Dian Kasih; Irvan Indrawan; Lies Setyowati; Munir Tanjung; Isra Suryati (Jurnal Dampak, 2018)
As the population increases, waste generation and composition will increase. Therefore, there is a need for planned and effective waste handling so that the problem of waste can be resolved in accordance with the 3R (Reuse, Reduce, and Recycle) concept. The aim of this research is to calculate the amount of waste generation and the composition of domestic waste produced by the residents of Medan Denai, and also devise the type of 3R Waste Treatment Plant for the District of Medan Denai. The method for measuring the generation and composition of waste are based on SNI 19-3964-1994, that is based on income level. Meanwhile, the typical planning of TPS 3R is obtained from the calculation of waste generation which is associated with the projection of population. The result showed that the average of household waste in the District of Medan Denai was 0.265 kg/person/day or 1.4 l/person/day. The composition of household waste generation in the District of Medan Denai is dominated by food waste 65.38 %. It is estimated that in 2026, the waste generation produced in the District of Medan Denai would reach about 41,593.7 kg/day. The economic potential that can be generated by using 3R concept is estimated reaching about Rp11,687,190 - Rp85,370,971 per day. Managing waste with 3R concept require a TPS with 1,488.24 m2 of area to process the household waste, with the estimated cost required to build the facility is Rp598,960,540 and the operational cost is Rp104,000,000 per month.